EKSISTENSI HUKUM ADAT DAYAK KALIMANTAN TENGAH DI ERA REVOLUSI INDUSTRI 4.0 - Jannatin Nisa ; Dahlianoor (Syarah: Jurnal Hukum Islam & Ekonomi, 2020)
Customary law is one of the laws that apply in Indonesia. The basic concept of customary law in central Kalimantan in the indigenous institutional Dayak in central Borneo that has been entered into the provincial regulation of central Kalimantan province No. 16 years 2008, and Central Kalimantan Governor regulation No. 13 year 2009. It is apparent that the customary law is a typical legal system and therefore differs from other legal systems, including the state's legal system as part of its legal state concept. So, it can be said that customary law is a system of law that is not as awake to the concept of the law state. This disbuilding can be seen from some differences that in the concept of the state of law, which becomes supremacy is the law of the State, while the customary law is not a state-made law, but rather the law that is born from the daily habits of society. The results of this study showed that the application of customary law in central Kalimantan, especially in central Teweh district, remained exist to be implemented until now in the midst of era of Industrial Revolution 4.0. Violations of this customary law are subject to singer sanctions. Sanctions are dropped if there is a violation of customary law that is money or other objects, such as feeding, cut pigs based on error rate.